Implementing Shadowing Technique to Improve the Eighth Grade Students’ Listening Comprehension At SMP St Petrus Medan in the Academic Year of 2022/2023 - Evi Romauli Sinaga; Fiber Yun Almanda Ginting; Meikardo Samuel Prayuda; Anna Stasya Prima Sari (ANFA MEDIATAMA, 2023)
This research was mainly conducted in order to prove that Shadowing technique could improve listening comprehension of the eighth grade students of SMP St Petrus Medan in the Academic Year of 2022/2023 and to describe their responses towards the implementation of Shadowing technique in the processes of learning listening comprehension. The quantitative data analysis showed the mean score increase from 53,9 in Pre-test with 27% of the students got score ≥72, in Formative-test 65,3 with 57% of the students got score ≥72, and 82,6 in Post-test with 93% of the students got score ≥72. Furthermore, the students’ responses toward the technique of the teaching learning process sound great because above 90% of the students are interested, motivated and understand the lesson with Shadowing technique. This is Classroom Action Research (CAR). The research findings showed that teaching listening comprehension by using Shadowing technique to the eighth-grade students of SMP St Petrus Medan could improve their listening comprehension. It is advisable that English teachers try applying Shadowing technique in teaching listening comprehension.